Growth and trade aspects of the proposed enlargement of the European Community - Juergen B. Donges (Kiel Institute of World Economics (IfW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 1978)
The purpose of this paper is to highlight significant growth and trade issues with respect to an eventual enlargement of the European Economic Community (EEC), after three Southern European economies formally applied for membership; Greece (on 12 June 1975), Portugal (on 28 March 1977), and Spain (on 28 July 1977). In the meantime, the EEC has entered into formal negotiations with Greece (since 27 July 1977) and Portugal (since 18 October 1978). The negotiations with Spain are expected to begin in spring 1979. The paper will first examine recent development trends in the three countries, assessing also the economic impact of the profound political changes which have taken place since the mid-seventies. Next, the structure of foreign trade and international competitiveness of the three economies will be analyzed. The last section will deal with some potential growth and trade implications of the EEC's enlargement from the point of view of the applicant's, the Community's and the third countries' interests.
Keywords: 330